Design and presence of activities on financial education in spanish primary education texts - Ferrada Ferrada, Cristian Andres (2021)
The purpose of this work is to analyze the activities related to Financial Education in the textbooks used in Primary Education, both in public and subsidized schools in the Autonomous Community of Andalusia, considering the OECD definition for financial competence. Through a qualitative methodological process, based on content analysis, an entire textbooks' series was studied for the subject of mathematics. The outcome showed the existence of 252 activities that agree with the Financial Education proposed model, highlighting the categories of money's value (145 activities) and state and citizens (133) with the greatest presence and, therefore, with the greatest development. According to this, we consider that a good culture in financial education in an early schooling facilitates the various economic decisions faced by students insituations of economic uncertainty.